Morphogenesis of the pancreas during the perinatal period of ontogenesis - Slobodian O.M. (Морфологія, 2008)
The purpose of the research – to establish the chronological sequence of changes of the ratios between the parameters of the pancreas and the parietocalcaneal length in embryos and newborns. The morphometric researches of the anatomical parts of the pancreas has been carried out on 57 fetal and newborn corpses in situ. Two periods of an accelerated development (months 5 and 8-10) and a period of a relative deceleration (months 6 and 7) have been revealed. An essential degree of synergism and a harmony of development between the morphometric parameters of the anatomical parts of the pancreas and the parietocalcaneal fetal length has been determined during the first period of an accelerated development (the 5th month). It was validated by correlation analysis and reliable multifactor regression dependence.